2018
DOI: 10.1016/j.gr.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The crustal architecture of Myanmar imaged through zircon U-Pb, Lu-Hf and O isotopes: Tectonic and metallogenic implications

Abstract: The Tethys margin in central and eastern Asia is comprised of continental terranes separated by suture zones, some of which remain cryptic. Determining the crustal architecture, and therefore the geological history, of the Eastern Tethyan margin remains challenging. Sited in the heart of this region, Myanmar is a highly prospective but poorly explored minerals jurisdiction. A better understanding of Myanmar's mineralization can only be realized through a better understanding of its tectonic history, itself ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 115 publications
1
36
0
Order By: Relevance
“…Modern river sands from the Upper Irrawaddy River draining the MMMB in northern Myanmar and in the Eastern Himalayan Syntaxis are dominated by Paleogene grains (Garzanti et al, 2016), display young grains (30–17 Ma) and are notably poor in pre‐Cretaceous zircons despite draining pre‐Cretaceous metamorphics, further suggesting that this area could be an important source. The occurrence of ultramafic and high‐grade metamorphic minerals, including the abundance of large detrital magnetite grains, in the Letkat deposits (section 4.2.2) and the appearance of Cenozoic zircons with negative εHf ( t ) values also support input from the MMMB (Gardiner et al, 2018). Finally, Ar‐Ar ages on MMMB rocks in northern Myanmar and in the Eastern Himalayan Syntaxis indicate early Miocene exhumation, coeval to AFT ages of Letkat sandstones (Bertrand et al, 2001; Haproff et al, 2019).…”
Section: Interpretationsmentioning
confidence: 85%
“…Modern river sands from the Upper Irrawaddy River draining the MMMB in northern Myanmar and in the Eastern Himalayan Syntaxis are dominated by Paleogene grains (Garzanti et al, 2016), display young grains (30–17 Ma) and are notably poor in pre‐Cretaceous zircons despite draining pre‐Cretaceous metamorphics, further suggesting that this area could be an important source. The occurrence of ultramafic and high‐grade metamorphic minerals, including the abundance of large detrital magnetite grains, in the Letkat deposits (section 4.2.2) and the appearance of Cenozoic zircons with negative εHf ( t ) values also support input from the MMMB (Gardiner et al, 2018). Finally, Ar‐Ar ages on MMMB rocks in northern Myanmar and in the Eastern Himalayan Syntaxis indicate early Miocene exhumation, coeval to AFT ages of Letkat sandstones (Bertrand et al, 2001; Haproff et al, 2019).…”
Section: Interpretationsmentioning
confidence: 85%
“… 207 Pb/ 204 Pb (i) against 206 Pb/ 204 Pb (i) (Fig. 5d in [1] ) Grid of εNd (t) including converted εHf (t) [Published data from [9] , [37] , [38] , [40] , [44] , [46] , [48] , [49] , [51] , [52] , [55] , [60] , [64] , [65] , [66] , [67] ]. (Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Garnier et al (2006) reported 40 Ar/ 39 Ar ages of 18.7-17.1 Ma for phlogopite in ruby-bearing marble near Mogok, which is 4 My older than our samples. The Kabaing microgranite yielded a magmatic U-Pb zircon age of 16.8 ± 0.5 Ma (Gardiner et al 2016(Gardiner et al , 2018, almost the same as the 16 Ma age reported by Searle and Haq (1964), and the biotite 40 Ar/ 39 Ar age of 15.8 ± 1.1 Ma reported by Bertrand et al (2001). Another similarly young age is the 16.1 ± 0.5 Ma, U-Th-Pb dating of zircon age for painite-bearing skarn at the contact between the Pingutaung leucogranite and marble (Thu 2007).…”
Section: Age Interpretationsmentioning
confidence: 99%